A Study of the Relationship of Genetic Polymorphisms of the PRL Gene with Milk Production and its Components in Holstein Friesian Cows - Raed Kawkab Al-Muhja; Muntaha Yacoob Yousief; Allawi Luaibi Dagher Al-Khauzai (Zien Journals, 2023)
Prolactin is a key regulator of milk production, mammary gland development, and milk protein gene expression . This study has been conducted in a laboratory Molecular Genetics of the College of Agriculture / University of Basrah. It aims at measuring the genetic polymorphism of milk production and its components, in Holstein Friesian cows. 59 Holstein Friesian cows from Taj Al-Nahrain station in AlDiwaniyah have been characterized for milk production and quality characteristics. Genomic DNA has been extracted from the blood and PCR has been used to amplify the PRL gene, then the amplification product has been purified and the samples have been analyzed by the Korean company Macrogene for DNA sequencing analysis. 50ml samples of morning milk have been collected on weekly basis and analysed for quality using the Milk analyzers Julie Z7 after collecting samples during the milking process. SPSS Statistical software has been used for association analysis. Gene shows the presence of a three genetic polymorphism in the breed of Holstein Friesian cows. The results show a significant the effect (p≤0.05) of the stage of milk production on each of the daily, and total milk production rate, while no differences have been shown of haplotypes on the rate of milk production. There have been no significant differences in the production stage in the proportions of fat, protein and milk sugar, while there has been a significant difference for the production stage on the total solids. In addition, no significant differences have been between shown of the haplotypes of the chemical composition of milk, except for the total solids
Keywords: Genetic Polymorphisms; PRL; Milk Production; Holstein Friesian Cows